Implementasi Pendidikan Ekonomi Syariah di SMP Alam Azzahra Way Jepara - Kurniasih, Apri; Hastuti, Nur (LPPM STAI DARUSSALAM LAMPUNG, 2024)
The purpose of this article is to describe the implementation of sharia economic education at SMP Alam Azzahra Way Jepara. The research was conducted using a qualitative phenomenological type approach. Findings in the research include: 1) Implementation of sharia economic education is carried out through implementing business learning as one of the school curriculum contents; 2) sharia economic education is carried out using a profit sharing approach; and 3) the form of muhdarabah carried out at the school includes the type of mudharobah muqayyadah.